Modeling evolution and dissemination of resistance under temporally changing antimicrobial concentration - Kubilay, Dilara Selin. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2018)
Quaternary ammonium compounds (QACs) are one of the most extensively used cationic biocides in human and animal health care facilities. Along with their many advantages as an antimicrobial agent, one of their biggest disadvantage is that QACs may facilitate development of antimicrobial resistance in bacteria which also promote antibiotic resistance at sub-inhibitory concentrations. Since QACs are biodegradable biocides, their concentrations may decrease substantially after they are applied to surfaces in hospitals. Thus, biodegradation creates environments with QACs at sub-inhibitory concentrations which are hotspots for evolution of QAC resistance. The objective of this study was to elucidate the role of biodegradation on the development of resistance to benzalkonium chlorides (BACs), one of the most extensively used group of QACs, by a BAC susceptible microorganism when a BAC degrader is present. Pseudomonas sp. BIOMIG 1 and a strain of E. coli were used as BAC degrader and BAC susceptible model organisms, respectively, in the experiments. E. coli growth was observed above the minimum inhibitory concentrations of BAC when BIOMIG 1 was present in the medium. Furthermore, E. coli's BAC resistance increased when this co-culture system was operated in a continuous reactor. Additionally, a model that simulates the dynamics of interactions in such a microbial community was developed, calibrated and verified successfully with the experimental data. Outcomes of this study may be useful to further explore processes involved in the evolution and dissemination of antimicrobial resistance in microbial communities in human health related environments.
Keywords: Ammonium compounds -- Environmental aspects.